Achilles tendon rupture: what you need to know. (2nd February 2021) - Biggs, A; Scott, G; Solan, MC; Williamson, M
Abstract : Heel pain and a history of a 'pop' or feeling 'something go' are the buzz phrases classically associated with Achilles tendon rupture. However, the diagnosis is often missed in clinical practice because of the assumption that this is a sporting injury suffered only by the young or middle-aged. In a sedentary older patient, the injury may be dismissed as an ankle sprain. If swelling is present but no injury is recalled then deep vein thrombosis is suspected, but Achilles rupture is not. The diagnosis of Achilles tendon rupture is clinical, based on history and examination. Radiological imaging (ultrasound scan) is useful to plan orthopaedic management and exclude concomitant deep vein thrombosis. In most cases, non-operative management with the ankle held plantar flexed in a boot is the current best practice.